Chapter Journey to a foreign land: imagining migration in Sinophone Literature from Thailand - Ehrenwirth, Rebecca (Studi e saggi, 2023)
Sima Gong and Zeng Xin are two of the most prominent contemporary Sinophone writers in Thailand. Although they were born in Thailand, they frequently write about migration. In this chapter I want to ask why the motive of migration is so prominent in their works and how they write about it. I argue that their ancestors' quest from China to Thailand is indeed not the focus of attention but the wandering between these two places. Although they did not physically migrate from China to Thailand, these authors use literature as a means to travel mentally between the two countries, and "re-live" the migratory experience through their texts. Analyzing these selected texts offers a unique insight into the authors' floating identity, one that is constantly migrating between China and Thailand.